UJI AKTIVITAS STIMULANSIA INFUSA DAUN COKELAT (Theobroma cacao L) PADA MENCIT PUTIH (Mus musculus) DENGAN METODE ROTAROD - Fadila, Vera Nurhidayatul; Ardiyantoro, Bagas; Listyani, Tiara Ajeng (JIFI (Jurnal Ilmiah Farmasi Imelda), 2025)
Fatigue due to excessive activity can be overcome with stimulants, but the use of synthetic stimulants carries the risk of side effects. This study aims to determine the stimulant activity of cocoa leaf infusion (Theobroma cacao L) and to determine the best dose that can increase central nervous system stimulation in white mice (Mus musculus). Synthetic stimulants often cause side effects, so natural alternatives are needed. This study tested the stimulant effect of cocoa leaf infusion (Theobroma cacao L.) on white mice (Mus musculus) using a rotarod test. Mice were divided into five groups: negative control (distilled water), positive control (caffeine 100 mg/kgBW), and infusion with doses of 50, 100, and 150 mg/kgBW. The results showed that all infusion doses significantly increased the survival time of mice compared to the negative control (p < 0.05). The dose of 150 mg/kgBW gave the effect closest to caffeine. Phytochemical tests showed the presence of alkaloids and flavonoids that are suspected to play a role in stimulant activity. Cocoa leaf infusion has the potential as a natural stimulant.